Evolution of Phenolic Composition During Barrel and Bottle Aging - Aleixandre-Tudo, J.L.; du Toit, W.J. (South African Journal of Enology and Viticulture, 2020)
During red wine ageing, phenolic compounds undergo several reactions that have an impact on wine colour and mouthfeel properties. The evolution of phenolic content is affected during wine ageing. The aim of this study was to investigate the phenolic content and evolution of 82 commercial red wines subjected to barrel and bottle ageing. The phenolic content evolution of wines that underwent an ageing period of 12 months in commercial 225 litre barrels, followed by 12 months in the bottle, was monitored. While the total phenolic content remained stable, the anthocyanin fraction was affected the most, which led to substantial changes in the colour properties of the wines. Differences were found during both ageing regimes, indicating certain phenolic reactions being favoured or compromised under different ageing conditions, with an impact on wine colour properties. This paper provides the first large-scale study on the phenolic evolution of commercial red wine during ageing.